Дослідження питань використання сучасного мультимедіа - Ярова, Ю. Д. (ХНУРЕ, 2020)
The justified and effective use of multimedia to support distance learning complements the analytical (computational and logical) capabilities of the computer with the ability to synthetically, figuratively and comprehensively represent the discipline.
Keywords: мультимедіа